2015
DOI: 10.5604/12321966.1152092
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence vs. health behaviour in selected groups in late adulthood

Abstract: The result of the study show that pro-health activities are directly associated with the abilities to understand and to control the emotions of older people. The data obtained confirm the positive relationship between the high level of emotional intelligence and pro-health behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…These results of health behaviours assessment are comparable with the results of other study groups. A similar result was obtained among older individuals (IHB -average score) [30,33], academic youth (IHB -mostly average, in some areas low) [3] and medical students in Lublin and Warsaw (IHB -average score) [25]. Analysis of the study results showed that among respondents the most common health behaviours were related to health practices, slightly less common in the area of positive mental attitude, and the least common in the area of proper eating habits and preventive behaviours.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These results of health behaviours assessment are comparable with the results of other study groups. A similar result was obtained among older individuals (IHB -average score) [30,33], academic youth (IHB -mostly average, in some areas low) [3] and medical students in Lublin and Warsaw (IHB -average score) [25]. Analysis of the study results showed that among respondents the most common health behaviours were related to health practices, slightly less common in the area of positive mental attitude, and the least common in the area of proper eating habits and preventive behaviours.…”
Section: Discussionsupporting
confidence: 85%
“…The intensity levels of health behaviours according to the Juczyński's IHB Questionnaire correlate significantly with the gender of the respondents. Authors' own research shows that the average level of health behaviours of men and women is diverse and is at an average level of 84.5; this is slightly lower than in the study of E. Sygit-Kowalkowska et al, which amounted to 86.8 [30]. Even higher results were obtained by researchers in 2011 in Sanok (E. Smoleń et al), where the overall IHB index was 88.39 [29].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous literature has shown several examples of intelligence affecting and modulating individual behavior, emotion and perception (Barry, 1997;Sternberg, 2000). For example, Sygit-Kowalkowska et al (2015) show a positive correlation between the level of emotional intelligence and pro-health behaviour such as observance of healthy diet and regular physical exercise in adult participants.…”
mentioning
confidence: 99%
“…High CQ employees can quickly adapt to their clients' or coworkers' cultures, which allows them to develop new ideas and initiate new activities (Darvishmotevali, Altinay, & De Vita, 2018). Thus, possessing emotional intelligence, which facilitates recognizing and regulating one's own and others' emotions, together with CQ, which focuses both on emotions and on intercultural interactions, results in new ideas and creative activity (Sygit-Kowalkowska, Sygit, & Sygit, 2015). Da Costa, Páez, Sánchez, Garaigordobil, and Gondim (2015) highlight that cognitive aspects such as CQ and emotional aspects such as emotional intelligence are more important for innovation in the workplace than motivational factors.…”
Section: Introductionmentioning
confidence: 99%